2008
DOI: 10.1080/00779950809544416
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand's ‘love affair’ with houses and cars∗∗

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…air travel. With the exception of meat, our expenditure elasticities are qualitatively consistent with the group-level expenditure demand elasticities from Khaled and Lattimore (2008)…”
Section: Cross-section Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…air travel. With the exception of meat, our expenditure elasticities are qualitatively consistent with the group-level expenditure demand elasticities from Khaled and Lattimore (2008)…”
Section: Cross-section Resultssupporting
confidence: 77%
“…The share of emissions from household utilities declines with household expenditure, while the share of emissions from transport increases. This is consistent with the results of Khaled and Lattimore (2008), who found that, in New Zealand, household utilities and operation are income inelastic, while transport is income elastic. Table 3 provides summary statistics for the 2006/07 and 2012/13 survey sample, as well as the pooled sample.…”
Section: Figure 1: Composition Of Average Household Emissions 2012/13supporting
confidence: 92%
See 2 more Smart Citations
“…As KiwiSaver is a nationwide auto-enrolment scheme, it has achieved significant attention in New Zealand. With over 2.1 million New Zealanders participating (52 per cent of the eligible total population as at May 2013), KiwiSaver is accredited with serving an educational role -raising the awareness and understanding of investment options outside and beyond the traditional New Zealand love affair with property investment (Khaled and Lattimore, 2008). This, in turn, fosters stronger domestic capital markets and growth of the economy.…”
Section: Introductionmentioning
confidence: 99%